Can real-time surveillance systems of suspected suicide accurately reflect national suicide rates? Age-specific and sex-specific findings from the first two years of the COVID-19 pandemic in England: an observational study - Nav Kapur; Louis Appleby; Pauline Turnbull; Su-Gwan Tham; Saied Ibrahim; Cathryn Rodway (BMJ Public Health)
Introduction ‘Real-time surveillance’ (RTS) systems of suspected suicide showed no overall rise in the early COVID-19 pandemic several months before official statistics reported the same. There has to date been no national examination of suicide recorded by RTS systems by sex or age group during the COVID-19 pandemic.Methods We used data from established RTS systems of suspected suicides in England, in 10 areas covering a total population ~13 million, to examine overall suicide numbers and rates from the pre-pandemic months of January–March 2020, to the end of 2021, by sex and by age group, through different phases of the pandemic.Results From January 2020 to December 2021, there were 2923 suspected suicides recorded by RTS systems in the 10 areas providing data. Using the pre-pandemic period as the baseline, we found a lower rate of suicide in the remainder of 2020 compared with the pre-pandemic period (0.80–0.99). This fall reflected lower numbers of deaths in men aged 25–44 between April and December 2020. Though there was no significant fall in 2021, there were lower rates in people aged 45–64 during this time. A month-by-month breakdown showed no change during periods of lockdown or social restrictions.Conclusions Our findings demonstrate the viability of RTS to provide timely information on suicide rates at a national level and were later confirmed by official statistics. While suicide rates have not increased, continued vigilance is needed given ongoing effects of the pandemic in the context of current economic pressures. Early data on suspected suicides collected by local systems can be instrumental in reflecting national trends, and in aiding a rapid response in times of crisis.